THE HEALTH DESCRIPTION OF CHILDREN AGED 12–24 MONTHS IN LOLOFITU-MOI SUB DISTRICT, NIAS DISTRICT IN 2006 - Jerico Franciscus Pardosi (Widyariset, 2011)
Nias District has under-five mortality rate of 66.3 per 1,000 live births in 2005 which is considered high. This study aimed to identify the health description of children aged 12–24 months in Lolofitu-moi sub district, North Sumatera Province. Cross sectional design was applied to measure children aged 12–24 months health status. This study is a cluster survey which was conducted from October 9 to 15, 2006. The survey sample included 97 mothers who have children aged 12–24 months in 5 villages by using LQAS method. Questionnaire was used for data collection. The results showed that 79 children sick, 19 children deaths before aged 12 months with 9 deaths occurred after aged 12 months. This study found that 9.3% children aged 12–24 months has low nutrition status.For immunization status, only 4 children out of 97 respondents has a complete immunization report. This study has recommended for Nias District Health Office to improve and strengthen children aged 12–24 months health care supported with regular health promotion for mothers.